PENGARUH OPINI AUDIT BPK DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Mega Nurhalimah; Dimas Wicaksono (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
This study analyzes the Effect of BPK Audit Opinion and Capital Expenditure on Local Government Financial Performance in West Java Province Cities and Regencies in 2018- 2021. This type of research uses quantitative research methods. The population and sample in this study were 108 cities and districts with a period of 4 years. The population and samples are West Java cities and regencies located in the Directorate General of Financial Balance, Ministry of Finance and the Financial Audit Agency which publishes the results of budget realization reports and inspection results. Retrieved from https://jabar.bpk.go.id and https://djpk.keimeinkeiui.go.id websites. The data analysis technique uses panel data regression analysis using Eviews 9.0 software. The results showed that the BPK Audit Opinion had a negative effect on the financial performance of local governments, while Capital Expenditure had a positive effect on the financial performance of local governments.